Peran Moderasi Kebijakan Utang pada Hubungan Pengungkapan Keberlanjutan dan Nilai Perusahaan - Nathania Davita; Winda Prajaningtyas; Amrie Firmansyah (Universitas Kristen Maranatha, 2022)
Investor response can be influenced by financial and non-financial information provided by Investor response can be influenced by financial and non-financial information provided by the company to the public. Information that is useful for investors can be used in making investment decisions. High company value is determined by investors' response in the capital market. This study examines the effect of sustainability disclosure on firm value, with debt policy as a moderating variable. This research data is sourced from financial reports, annual reports, sustainability reports and stock prices of manufacturing companies for the period 2018-2020 obtained from www.idx.co.id, www.finance,yahoo.com, and the company's official website. This study used 366 observations determined by using the purposive sampling technique. Hypothesis testing is done by using multiple linear regression analysis for panel data. The result suggests that the sustainability disclosure has no effect on firm value. Also, debt policy cannot moderate sustainability disclosure on firm value. This research indicates that the Financial Services Authority needs to monitor the sustainability implementation by listed companies on the Indonesia Stock Exchange. Keywords: Corporate Social Responsibility, Investor Response, and Capital Structure